Impact of the COVID-19 pandemic on the mental and physical health of Indian working women: A cross-sectional study of District Rajkot, Gujarat - Thakur Dev PANDEY; Jyoti PATHAK (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: The COVID-19 pandemic has profoundly affected societies and economies worldwide, with working women facing unique challenges. This study aimed to analyze changes in the employment status of working women before and after the COVID-19 pandemic, identify the challenges and barriers they faced, assess the impact of remote work on career progression, and examine the effects on their mental health and well-being. The study also aimed to address these challenges by proposing policies and support systems to promote gender equality, work-life balance, mental health support, and career advancement opportunities for working women in Rajkot District, Gujarat. Methods: This cross-sectional study collected primary data through administered surveys and interviews with working women from various industries in Rajkot District. The sample size was determined using Cochran’s Formula, resulting in 364 valid responses after excluding incomplete data. Quantitative data were analyzed using descriptive statistics and chi-square tests, while qualitative data were examined using thematic analysis. Results: Pre-COVID-19 data indicated stable employment rates across the talukas, with significant portions facing financial strain and mental health issues. Post-COVID-19 data revealed a substantial increase in unemployment, challenges, and the need for psychological counseling. The chi-square analysis highlighted significant changes in employment status, career progression, mental stability, and the demand for mental health support. Single mothers and low-income groups were particularly affected, experiencing heightened challenges related to balancing work and caregiving responsibilities, accessing healthcare, and maintaining financial stability. Discussion: The findings underscore the urgent need for targeted policy interventions to support vulnerable groups, including single mothers and low-income women. Recommendations include childcare support initiatives, flexible work policies, affordable healthcare access, and targeted financial assistance programs. These measures are essential to mitigate the long-term socioeconomic effects of the pandemic and promote a more inclusive and equitable recovery. Future research should focus on longitudinal studies to track the recovery and adaptability of working women, ensuring ongoing support and resilience in the workforce.